The application of an analytical model to solve an inverse heat conduction problem: Transient solidification of a Sn-Sb peritectic solder alloy on distinct substrates - Curtulo, Joanisa P.; Dias, Marcelino; Bertelli, Felipe; Silva, Bismarck L.; Spinelli, José E.; Garcia, Amauri; Cheung, Noé (Journal of manufacturing processes, 2019)
[Display omitted] •A thermal/experimental approach is proposed to analyze solder/substrates interaction.•A Sn-Sb solder solidified against three substrates gives experimental support to the approach.•Wettability is shown not to be the only important parameter for solder/substrate interaction.•A thermal analytical model can preview voids at the alloy/substrate interface. Three distinct alloy/substrate couples were considered. In order to treat the reaction interface problem effectively, sheets of commercially pure copper (Cu), electrolytic nickel (Ni) and low carbon steel were chosen so that solidification of a Sn-Sb peritectic alloy could be evaluated comprehending very different conditions. A straightforward view of the mechanisms affecting the heat transfer efficiencies was consistent with a number of techniques applied in the present investigation, which includes directional solidification experiments, analytical modelling, wettability analyses and characterization of the reactions between the alloy and the substrates. The proposed analytical model was perceptive to these reactions. For the Cu substrate, the motion of Cu towards the alloy was more effective as compared to the motion of Ni from the Ni substrate. As a consequence, the alloy/Cu interface presented a higher level of Kirkendall voids. The higher fraction of voids at the interface resulted in lower interfacial thermal conductance for the Sn-Sb/Cu couple. Hence, the present experimental-theoretical approach is useful to indicate the solder joint integrity in terms of the presence of empty spots. Despite the higher thermal conductivity of Cu and lower contact angle between the alloy and the Cu in comparison to the Ni substrate, the high porosity at the Cu interface during alloy soldering was shown to reduce the heat transfer capability.